Uji Aktivitas Antibkteri Ekstrak Etanol Daun Kemangi (Ocium Sanctum L) Asal Desa Ureng Kabupaten Maluku Tengah Terhadap Pertumbuhan Bakteri Staphylococcus epidermis - Amelia Niwele; Aulia Debby Pelu; Laitupa Hardiyanti L (Universitas Muhammadiyah Manado, 2021)
One of the plants that can use drugs is the (Ocimum Sanctum Linn). Basil leaves are one of the many available and readily available natural plants in Asia such as Indonesia.In addition to using it as fly,basil leaves are used as bronchitis,malaria,diarrhoea,skin disease,and so on.Studies have been conducted on the test of the leaf’s antibacterial ethanol (Ocimum Sanctum Linn) for the growth of the staphylococcus epidermis bacteria by using the diffusion method for the commonwealth.The study is to identify the extract of basil leaf ethanol (Ocimum Sanctum Linn) that gives resistance to bacteria. Basil leaves (Ocimum Sanctum Linn) in extraction by means 0f a 96% ethanol solducer. The results of the extraction are then in the screening of antibacterial activity at a concentration 25%,50%,and 100%. Tests obtained indicate that ethanol extract is 96% of basil leaves (Ocimum Sanctum Linn) cannot prevent the growth of the staphylococcus epidermis bacteria. The false factor derived from the powdered leaf ethanol extract (Ocimum Sanctum Linn) is influenced by mildew suspension,milquetide exposure to media,incubation temperatures,incubation times,media thickness,and media composition.